Usefulness of Video Review of Possible Concussions in National Youth Rugby League - Gardner, A. J.; Kohler, R. M. N.; Levi, C. R.; Iverson, G. L. (International Journal of Sports Medicine, 2017)
A new concussion interchange rule (CIR) was introduced in 2014 for the National Rugby League and National Youth Competition (NYC). The CIR allows a player suspected of having sustained a concussion to be removed from play and assessed without an interchange being tallied against the player’s team. Participants included all NYC players who used the CIR during the 2014 season. 2 raters completed video analysis of 131 (of a total of 156 reported) uses of the CIR, describing injury characteristics, situational factors, and concussion signs. The incidence rate was 44.9 (95% CI: 38.5–52.3) uses of the CIR per 1 000 NYC player match hours, or approximately one CIR use every 1.3 games. Apparent loss of consciousness/unresponsiveness was observed in 13% of cases, clutching the head in 65%, unsteadiness of gait in 60%, and a vacant stare in 23%. Most incidences occurred from a hit-up (82%). There appeared to be some instances of video evidence of injury but the athlete was cleared to return to play in the same game. Video review appears to be a useful adjunct for identifying players suffering possible concussion. Further research is required on the usefulness of video review for identifying signs of concussive injury.
Keywords: concussion; video analysis; injury management; return to play